Motivational components in TIMSS 2015 and their effects on engaging teaching practices and mathematics performance. (September 2022) - Ivanova, Militsa; Michaelides, Michalis P.
Abstract: Student motivation is a multifaceted construct with empirically supported associations with educational outcomes. This study used latent variable methodology to examine the factor structure of the engaging teaching and motivational constructs in the fourth- and eighth-grade USA student context questionnaires of the 2015 Trends in International Mathematics and Science Study (TIMSS). Measurement models revealed adequate fit of correlated factors for self-concept, enjoyment, and importance and usefulness of learning mathematics, after controlling for negative wording. Self-concept was the strongest predictor of achievement in both grades; importance and usefulness beliefs had a weak relationship with eighth-grade performance. Engaging teaching and enjoyment were positively associated; accounting for self-concept, the effect of engaging teaching on TIMSS performance was negative and mediated by enjoyment. The results suggest that a multifaceted conceptualization of motivation is needed in studies of student achievement. The strong effect of student self-concept on performance should be acknowledged in educational reforms. Highlights: Contextual variables measured in TIMSS include motivational constructs. Self-concept in mathematics is the strongest motivational predictor of performance. Engaging teaching behavior positively relates to student enjoyment of mathematics. Controlling for self-concept, enjoyment and engaging teaching negatively predict performance.